2017
DOI: 10.3906/sag-1512-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum uric acid levels in psoriasis vulgaris

Abstract: IntroductionPsoriasis is an inflammatory and immune-mediated papulosquamous disease with unknown etiology. It is characterized by abnormal epidermal hyperproliferation and differentiation, and it affects 1%-2% of the population (1).Uric acid is an endogenously produced end-product of adenosine-and guanosine-based purine metabolism (2). A number of studies showed strong correlation among high uric acid levels, insulin resistance, and metabolic syndrome, which has been suggested to develop secondary to insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 10 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…Conflicting evidence was available for 14 of 137 laboratory markers: markers of bone metabolism (Dickkopf (DKK1) [ 52 , 53 ]; RANK-L [ 49 – 51 , 53 , 56 , 57 ]), markers of lipid metabolism (serum leptin [ 64 , 71 ]; total serum cholesterol [ 42 , 62 , 71 , 76 , 77 ]; total cholesterol: HDL ratio [ 42 , 76 ]; serum triglycerides [ 42 , 71 , 72 , 76 , 77 , 130 ]), inflammation markers (erythrocyte sedimentation rate (ESR) [ 43 , 44 , 47 , 56 , 62 , 66 , 70 , 74 , 75 ], cell numbers (platelet count [ 68 , 70 ]; white blood cell count [ 70 , 130 ]), cell phenotype (IL-17 secretion [ 58 , 59 ]), cytokine levels (IL-12/23 p40 [ 49 , 56 ]; macrophage colony-stimulating factor (M-CSF) [ 52 , 53 ]), uric acid [ 77 , 86 88 ], and antibodies against LL-37 [ 82 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting evidence was available for 14 of 137 laboratory markers: markers of bone metabolism (Dickkopf (DKK1) [ 52 , 53 ]; RANK-L [ 49 – 51 , 53 , 56 , 57 ]), markers of lipid metabolism (serum leptin [ 64 , 71 ]; total serum cholesterol [ 42 , 62 , 71 , 76 , 77 ]; total cholesterol: HDL ratio [ 42 , 76 ]; serum triglycerides [ 42 , 71 , 72 , 76 , 77 , 130 ]), inflammation markers (erythrocyte sedimentation rate (ESR) [ 43 , 44 , 47 , 56 , 62 , 66 , 70 , 74 , 75 ], cell numbers (platelet count [ 68 , 70 ]; white blood cell count [ 70 , 130 ]), cell phenotype (IL-17 secretion [ 58 , 59 ]), cytokine levels (IL-12/23 p40 [ 49 , 56 ]; macrophage colony-stimulating factor (M-CSF) [ 52 , 53 ]), uric acid [ 77 , 86 88 ], and antibodies against LL-37 [ 82 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extent of skin involvement, as measured by the PASI score, was not associated with HUC in the current study. Previous literature has provided some conflicting results as to whether HUC is related to the severity of psoriasis 8,10,11 or metabolic dysregulation 21,22 . It was reported that the serum uric acid is 1 of the determinants of the metabolic syndrome in nonpsoriatic patients; with 1 unit increase of serum uric acid, the odds of developing metabolic syndrome roughly doubled 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown a correlation between HUC and psoriasis, results were conflicting 10,11,12 . It is not clear whether HUC is correlated with the extent of skin involvement, or whether it results from the effects of coexisting features of the metabolic syndrome.…”
mentioning
confidence: 99%
“…The metaanalysis consisted of two parts based on the type of response variable. The first part included the 27 studies (10,11,(14)(15)(16)(17)(18)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) that used continuous SUA as the response variable. These studies consisted of 31,314 participants (2,951 with psoriasis and 28,363 controls).…”
Section: General Characteristics and Methodology Assessmentmentioning
confidence: 99%